Ukraine since the Orange Revolution : a business and investment review - Terterov, Marat (Global market briefings., 2006)
This in-depth progress report on market reforms and the changes to law and commercial practice being instituted by Ukraine's new government, offers an insider's guide to the current investment climate and the risks and opportunities for foreign investors in Ukraine. It gages the opinions of economic and political analysts, lawyers and the foreign investor community on Ukraine's business and investment environment. The new government's policy objectives included combating corruption and business cronyism, creating a more attractive environment for foreign investment, and moving Ukraine closer t.